CALL in Post-Method Era - Hussien M. Abdo Almaktary; Abdu M. Talib Al-Kadi (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2017)
This paper touches on the influx of technology in language learning and teaching with a focus on the post-method era. Scrutinizing this phenomenon within the framework of Computer-Assisted Language Learning (CALL) shows how technology has stimulated a transformation of language pedagogy from the traditional teacher-centered and text-bound classrooms to student-centered and interactive paradigms. While the former paradigm is based on methodology, the latter is guided by principled eclecticism in which teachers make use of a set of macro-strategies so as to make decisions while teaching, instead of reliance on methods that dictate ‘how to teach’. The teaching principles capitalize on teachers’ sensitivity to local contexts rather than general methods. Though CALL has been mooted as panacea for ELT flaws in the method and post-method eras, it is not a one-size-fits-all model. Due to changeable and diversified technological innovations, it is impractical to adopt an electronic device or application for all contexts. Accordingly, the post-method pedagogy puts the onus on language teachers to make informed choices that best fit the particularity of their teaching situations.